Issue Competence and its Influence on Voting Behavior in the Swiss 2015 Elections. Issue 1 (1st March 2016) - Lutz, Georg; Sciarini, Pascal
Abstract: The Liberal Radical party and – even more so – the Swiss People's party are the two winners of the Swiss 2015 election. In this contribution, we evaluate whether and to what extent issue ownership voting may help to account for the electoral success of these two parties. To that end, we distinguish the two dimensions – the associative and the competence dimension – of the concept and we rely on data from the on‐line, four‐wave panel survey carried out in the context of the Swiss election studies. Our results highlight the stability of issue ownership perceptions during the course of the campaign on the aggregate level, but they also show the substantial importance of issue ownership voting, on the individual level. More specifically, in line with earlier studies we find that competence issue ownership has a direct impact on the vote choice, whereas the impact of associative issue ownership is far more limited. For both parties under study, being seen as the most competent party on two important issues (migration and the economy) significantly contributes to the explanation of the vote choice.